La región, red global y la ciudad frente a una caracterización del desarrollo de la metrópoli barranquilla (2013)
The article arises from the concern of “sustainable development expertise and the environment” by the search for incidents in the urban-metropolitan net and the critical concepts of the sustainable economic development. This allowed to make the thinking of some sensitive themes regarding the regional, global, metropolitan context from the economical, social, environmental and especially urban visions. Think and consider, that characterizes the relationship? Determine a region?, Global network? or What, the city developed as a metropolitan area? or, What impacts have been generated due to the growth and management of the metropolis, this latest in the District of Barranquilla. This approach aims to provide supporting evidence to guide inquiry, related both theoretically and politically.